Induction of Multiple Immune Regulatory Pathways with Differential Impact in HCV/HIV Coinfection - Cho, Hyosun; Kikuchi, Masahiro; Li, Yun; Nakamoto, Nobuhiro; Amorosa, Valerianna K.; Valiga, Mary E.; Chang, Kyong-Mi (Frontiers in Immunology, 2014)
Persistent viral infections including HCV, HBV and HIV are associated with increased immune regulatory pathways including the extrinsic FoxP3+ CD4+ regulatory T-cells (Tregs) and intrinsic inhibitory pathways such as programmed death-1 (PD-1) and cytotoxic T-lymphocyte antigen 4 (CTLA4) with potentially reversible suppression of antiviral effector T cells (1-12). Immunological consequences of viral coinfections relative to these immune regulatory pathways and their interplay are not well defined. In this study, we examined the frequency, phenotype and effector function of circulating T cell subsets in patients with chronic HCV and/or HIV infection, hypothesizing that HCV/HIV-coinfection will result in greater immune dysregulation with pathogenetic consequences (13, 14). We show that multiple T cell inhibitory pathways are induced in HCV/HIV coinfection including FoxP3+ Tregs, PD-1 and CTLA-4 in inverse association with overall CD4 T cell frequency but not with liver function or HCV RNA titers. The inverse association between CD4 T cell frequency and their FoxP3, PD-1 or CTLA-4 expression remained significant in all subjects combined regardless of HCV and/or HIV infection, suggesting a global homeostatic mechanism to maintain immune regulation relative to CD4 T cell frequency. PD-1 blockade rescued T cell responses to HIV but not HCV without significant impact by CTLA-4 blockade in vitro. Collectively, these findings highlight complex immune interactions in viral coinfections and differential regulatory pathways influencing virus-specific T cells that are relevant in immunotherapeutic development.